Compound development of fe80cr20 metallic interconnect by ball milling and ultrasonic technique: its effect on mass gradation - Dafit Feriyanto; Hadi Pranoto; Dedik Romahadi; Imam hidayat; Spaatz Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2023)
The investigation of metallic material for interconnect fuel cell application was very challenging due to interconnect operate at high temperature up to 11000C. However, the main problem of metallic material is mass change at high temperature is inevitable. Therefore, this research aims to analyse the compound of Fe80Cr20 and it effect of mass gradation. The methods were conducted by ultrasonic technique (UT) by frequency of 35 kHz, various ultrasonic time of 3, 3.5, 4, 4.5 and 5 h. Milling technique was conducted by milling time of 60 h with nitrogen gas condition. The analysis was conducted by Scanning Electron Microscope for compound investigation and Thermo Gravimetric Analyzer (TGA) for mass gradation analysis. The result shows that there are several compounds that developed after ball milling and ultrasonic technique such as Fe80Cr20, FeO2 and Cr2O3. The UT samples shows the lowest mass gain of 31.917 mg is located at UT 4.5 h, while raw material has largest mass gain as compared to the other samples (treated samples). Meanwhile for milled and combination of milled and UT samples shows the lowest mass gain has observed at milled and UT 4.5 h with the value of 17.014 mg and 12.7 mg, respectively.